2017
DOI: 10.1016/j.jacc.2016.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Imaging, Cholesterol Efflux, and Transcriptomes After Intensive Statin Treatment

Abstract: The study demonstrated an independent association between fibrous cap thickening and improved CEC that may contribute to morphological changes suggesting plaque stabilization among patients taking intensive statin therapy. Furthermore, the significant perturbations in PBMC transcriptome may help determine the beneficial effects of statin on plaque stabilization. (Reduction in Coronary Yellow Plaque, Lipids and Vascular Inflammation by Aggressive Lipid Lowering [YELLOW II]; NCT01837823).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 50 publications
3
49
1
Order By: Relevance
“…Since these structural changes are related to underlying disease aetiology and pathophysiological mechanisms, imaging is obviously widely used in cardiovascular medicine 5. Imaging data sets are complex and stored in a variety of formats (JPEG, MPEG, DICOM, and so on) and are of varying dimension and scale (two dimensional, three dimensional, four dimensional, and so on), thereby representing the leading edge of cardiovascular big data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since these structural changes are related to underlying disease aetiology and pathophysiological mechanisms, imaging is obviously widely used in cardiovascular medicine 5. Imaging data sets are complex and stored in a variety of formats (JPEG, MPEG, DICOM, and so on) and are of varying dimension and scale (two dimensional, three dimensional, four dimensional, and so on), thereby representing the leading edge of cardiovascular big data.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular profiling and downstream analyses using statistical and machine learning approaches can also aid in identifying new target molecules for drug discovery and drug repositioning 5 14. Emerging studies suggest that combining pan-omics technologies with imaging will be routine in the future to compile a stratified profile of patient population 5. For example, recently, Li et al demonstrated that layering genomic data on EHR-based phenomics can be used to find and characterise patient subtypes (in this case, for type 2 diabetes mellitus) 15…”
Section: Introductionmentioning
confidence: 99%
“…However, pharmacological intervention aiming to raise serum HDL-C levels failed to reduce the incidence of cardiovascular disease events as assessed in several randomized controlled trials. Study by Hafiane et al supposed that HDL-C mass did not reflect HDL functionality and macrophage-specific cholesterol efflux to apo A-I particles binding to the ABCA1 is considered the most relevant to atherosclerosis [26]. Cholesterol efflux from macrophages is considered a crucial step of reverse cholesterol transport that is responsible for maintaining normal cholesterol balance.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence demonstrated that CEC had an inverse relationship with incidence of cardiovascular events in population-based studies and CEC improve cardiovascular disease risk prediction beyond conventional risk factors [26]. It was also concluded that measures of HDL function might be a better marker of cardiovascular risk and, possibly, of recurrent events than are HDL cholesterol levels [27].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of statin therapy on HDL metabolism is less clear. Previous reports have shown that statins may both decrease [51,52] or increase [53] CEC -the only metric of HDL functionality that has been shown to be predictive of prospective CVD events. A recent study showed that on-statin CEC was inversely associated with incident cardiovascular events and that, in fact, HDL particle number was the strongest HDLrelated biomarker of residual risk in statin-treated patients [54].…”
Section: Discussionmentioning
confidence: 99%